2021
DOI: 10.2196/26564
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrocannabinol and Skin Cancer: Analysis of YouTube Videos

Abstract: Background Cannabis oil is being used topically by patients with skin cancer as a homeopathic remedy, and has been promoted and popularized on social media, including YouTube. Although topical cannabinoids, especially tetrahydrocannabinol (THC), may have antitumor effects, results from a sparse number of clinical trials and peer-reviewed studies detailing safety and efficacy are still under investigation. Objective We sought to assess the accuracy, qual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The use of video broadcasting sites as a source of information about malignant tumors, such as colorectal cancer [ 18 ], thyroid cancer [ 19 ], larynx cancer [ 20 ] and skin cancer [ 21 ], has been evaluated. Many studies have reported that video broadcast sites have positive and negative effects on health information dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…The use of video broadcasting sites as a source of information about malignant tumors, such as colorectal cancer [ 18 ], thyroid cancer [ 19 ], larynx cancer [ 20 ] and skin cancer [ 21 ], has been evaluated. Many studies have reported that video broadcast sites have positive and negative effects on health information dissemination.…”
Section: Discussionmentioning
confidence: 99%